MICROSOFT OFFICE 365-A1 AS ONLINE ENGLISH TEACHING MEDIA IN ACADEMIC READING LESSON - Prasongko, Angga; Kurniawan, Erwin Hari; Muchyidin, M. Syaichul (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
Education is one of the sectors of life that has been affected by the global pandemic. As an attempt to stop the spread of the Covid-19 virus, one of the policies implemented by the Indonesian Ministry of Education is online learning. It is can be a triggered acceleration of education digitalization in Indonesia. Technology-based learning media and applications have been applied at the Universitas Islam Kadiri (UNISKA Kediri) during online learning in the pandemic era. UNISKA Kediri develops learning media in the form of a Learning Management System (LMS UNISKA) based on Moodle for lecture activities. One of the popular teaching media used as online learning is Microsoft Office 365 A1. This research aimed to prove the use of Microsoft Office 365 - A1 as online English teaching and learning media, especially in academic reading lesson and its challenges. The research was carried out at the English Education study program, Faculty of Teacher Training and Education, UNISKA Kediri. This study uses a qualitative descriptive approach. The data collection was carried out by interview, field observation and documentation. After data collection. The data validation through a data triangulation process with a source triangulation model. The results showed that the implementation of teaching and learning using Microsoft 365 – A1 in academic reading lesson have been applied during the COVID-19 pandemic, the obstacles both lecturer and students have problem on their ability for adapting the habitual in online teaching and learning process. From the study can be concluded that using Office 365 A1 on Academic Reading in the English Education study program UNISKA Kediri helps students in conducting online lectures during the COVID 19 pandemic. The use of learning media according to the needs of learners is very effective in achieving learning objectives.